(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing integration of Artificial Intelligence (AI) in higher education has transformed academic research practices, particularly in literature review, data analysis, and research writing. This study investigated the factors influencing the use of AI tools in academic research among junior and senior students of the College of Computer Studies at Quezon City University. Specifically, it examined the respondents’ demographic profile, level of AI tool utilization, factors affecting AI adoption, barriers to AI usage, and the relationship between these factors and students’ actual AI usage behavior. The study employed a quantitative descriptive-correlational research design and utilized an online survey questionnaire administered to 130 students from the BS Information Technology, BS Information Systems, and BS Computer Science programs using stratified sampling. Descriptive statistics, Pearson Product-Moment Correlation, and Multiple Regression Analysis were used to analyze the collected data. Findings revealed that students demonstrated a moderate level of AI tool utilization in research activities, with perceived usefulness emerging as the most influential factor affecting AI adoption. Students commonly used AI tools for idea generation, information retrieval, and writing assistance; however, AI utilization remained limited due to concerns related to plagiarism, data privacy, ethical misuse, overdependence on AI-generated outputs, and insufficient institutional support. The study also found a significant relationship between the identified adoption factors and students’ actual AI usage behavior. Overall, the findings suggest that AI tools have strong potential to improve research productivity and efficiency, but educational institutions must establish clear policies, governance frameworks, and training programs to ensure the responsible, ethical, and effective integration of AI in academic research.